Agar.io: The Game's in the Name. Issue 2 (March 2019) - Lindsey, Cameron
Agar.io is a web and app game with simplistic rules and a minimalistic design. Despite this, the game grew to great global prominence in 2015, and the narratives players constructed within the game had great sociopolitical implications from its affects on web culture and even to national political campaigns. This article points to the leaderboard and the ability to broadcast messages to other users through player usernames as the primary reason for the game's success as a platform for users to broadcast messages. Agar.io, through usernames and omnipresent leaderboards broadcasting these names, affords players the chance to put their ideologies and allegiances in competition through a simulation of a "survival of the fittest" cell culture. Through a formal analysis of the game this article shows that, for Agar.io, the game is in the name(s).